PENINGKATAN MINAT DAN HASIL BELAJAR BILANGAN BERPANGKAT DAN BENTUK AKAR SISWA KELAS X TEKNIK SEPEDA MOTOR SMK ELEKTRO SIJUNJUNG DENGAN MENGGUNAKAN PETA KONSEP - Dewi Sefriyanti (JURNAL SAINTIKA UNPAM, 2019)
This study aims to increase students' interest and mathematics learning achievements on the subject of rank numbers, root shapes and logarithms. In this study I used a concept map. Concept maps are a tool in the form of a scheme that states the relationship between concepts starting from the general to the specific ones which are connected through arrows in the form of propositions. Proposition is two or more statements about a concept that are related to words or arrows. Concept maps play an important role in meaningful learning, with concept maps of students being trained to think, in students being asked to think about concepts or events they already know. Meaningful learning is easier to take place if new concepts are linked to concepts that are inclusive, inclusive concepts that are basic concepts that are more general in nature. Concept maps must be arranged in a hierarchical manner, which means that a more inclusive concept is at the top of the map, the concepts below are sorted into less inclusive ones.